The roles of Cryptochrome-1: the circadian clock as a control point in cancer therapy - Yijia Liu; Yanzhe Huang; Hongliang Luo; Xueqin Lin (Journal of Translational Medicine)
Abstract In this review, we carefully describe the composition and operation of cryptochrome-1 (CRY1). We introduce four related signaling pathways, namely cAMP/PKA/CREB signaling way, HIFα signaling way, NF-κB signaling way, STAT3 signaling way, FOXO signaling pathway and Hedgehog (HH) signaling pathway. We also emphasize the current understanding of the complex roles CRY1 plays in the progression of various solid tumors. We propose that its function represents a novel therapeutic target that could pave the way for new cancer treatments. Additionally, we summarize three emerging therapeutic strategies based on the roles of CRY1: targeting CRY1 with small molecules, using CRY1 as diagnostic and therapeutic tools, and promoting drug efficacy through CRY1 modulations. It is imperative to underscore the significance of conducting more extensive research to translate the insights obtained from cellular and animal models into practical human applications, ultimately enhancing therapeutic outcomes.